PREPARATION AND IN VITRO EVALUATION OF METOPROLOL-LOADED BOVINE SERUM ALBUMIN NANOPARTICLES - YELLANKI, SHIVA KUMAR; MANOJ A, SAI; T, MANGILAL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim of the present research was to prepare metoprolol-loaded nanospheres. Metoprolol-loaded bovine albumin nanospheres were prepared by nanoprecipitation method. Metoprolol is beta-1-adrenergic receptor inhibitor specific to cardiac cells, thus producing negative chronotropic and ionotropic effect. Methods: Metoprolol nanospheres were prepared by nanoprecipitation method, using bovine serum albumin as polymer. The prepared nanospheres are evaluated for particle size evaluation, drug entrapment efficiency, and zeta potential. Drug-excipient compatibility was determined using Fourier-transform infrared spectroscopy. In vitro release and solubility of the drug from nanoparticles were determined. Results: The particle size of prepared metoprolol nanospheres was found to be always less than 200 nm. Maximum particle size was found to be 196±2.03 nm of batch 4 nanoparticles. Entrapment efficiency of prepared nanospheres was above 80% and maximum percentage entrapment efficiency was found to be 80.4±0.51%. It was found that the percentage entrapment efficiency and drug release were extended with increase in polymer concentration. Zeta potential of the optimized formulation was found to be −20.4 mV. In vitro drug release studies have shown the prolonged release of 94.5±0.54 up to 10 h. Drug release rate is extended with an increase in polymer concentration. Conclusion: Results have concluded that the albumin nanospheres loaded with metoprolol have reduced the blood pressure within 24 h and the prepared nanospheres are effective compared to other formulations and drug delivery.